The incidence of first venous thromboembolism in and around pregnancy using linked primary and secondary care data: a population based cohort study from England and comparative meta-analysis - Sultan, Alyshah Abdul; Tata, Laila J.; Grainge, Matthew J.; West, Joe (Public Library of Science, 2013)
Background: Recent linkage between primary and secondary care data has provided valuable information for studying heath outcomes that may initially present in different health care settings. The aim of this study was therefore, twofold: to use linked primary and secondary care data to determine an optimum definition for estimating the incidence of first VTE in and around pregnancy; and secondly to conduct a systematic literature review of studies on perinatal VTE incidence with the purpose of comparing our estimates.